KECEMASAN MAHASISWA MENGHADAPI OBJECTIVE STRUCTURAL CLINICAL EXAMINATION (OSCE) - Rahmawati Sri Praptiningsih (ODONTO : Dental Journal, 2016)
Background: OSCE is a clinical examination to test students’ skill. Students have to demonstrate skill possessed by the different conditions and examined by a particular examiners. The condition potentially the students suffering of anxiety in which symptoniced by phsichologies as students’ scared, felt nervous insecure. Impacts of anxiety caused reduction of students’ skill in pursuing their tasks thereby get the bad result .Purpose: To find out the correlation between anxiety and OSCE gradeMethod: This research is a quantitative descriptive research with cross sectional method,. Samples were taken from all second and third year students as many of 135 students who participated in OSCE. To investigate, the researcher used two kinds of research instruments, OSCE checklist and anxiety rating scale which were filled by students, then it was conducted statistics test using Pearson Product Moment correlation test.Results: Anxiety score in this research was about 73-141, with an average 100,66 and deviation standard 12,55, whereas OSCE grade showed that the lowest score was 40 and the highest was 92 with the average 71,5; deviation standard 10,52 and the probability > 0,001 (0,396>0,01). Conclusion: Most of students suffered nervous when facing OSCE. After analyzing through Pearson correlation test was obtained that there was not any positive correlation between students’ anxiety and OSCE grade. And there was significancy different between the first year and the third year